Length scales and statistical characteristics of outer bank roughness for large elongate meander bends: The influence of bank material properties, floodplain vegetation and flow inundation. Issue 13 (15th June 2017) - Konsoer, Kory; Rhoads, Bruce; Best, James; Langendoen, Eddy; Ursic, Mick; Abad, Jorge; Garcia, Marcelo
Abstract: This article explores the length scales and statistical characteristics of form roughness along the outer banks of two elongate bends on a large meandering river through investigation of topographic variability of the bank face. The analysis also examines how roughness varies over the vertical height of the banks and when the banks are exposed subaerially and inundated during flood stage. Detailed data on the topography of the outer banks were obtained subaerially using terrestrial LiDAR during low flow conditions and subaqueously using multibeam echo sounding (MBES) during near‐bankfull conditions. The contributions of various length scales of topographic irregularity to roughness for subaerial conditions were evaluated for different elevation contours on the bank faces using Hilbert–Huang Transform (HHT) spectral analysis. Statistical characteristics for discrete areas on the bank faces were determined by calculating the root‐mean‐square of normal distances from a triangulated irregular network (TIN) surface. Results of the HHT analysis show that the characteristics of roughness along bank faces composed primarily of non‐cohesive sediment, and eroding into cropland, vary with bank elevation and exhibit a dominant range of roughness length scales ( 15–50 m). However, bank faces composed predominantly of cohesive material and carved into a forested floodplain have relatively uniform topographic roughness characteristics over the vertical extent of the bank face and do not exhibit a dominant roughness length scale or range of length scales. Additionally, comparison between local surface roughness for subaerial versus subaqueous conditions shows that roughness decreases considerably when the banks are submerged, most likely because of the removal of vegetation and eradication of small‐scale erosional features in non‐cohesive bank materials by flow along the bank face. Thus, roughness appears to be linked to the hydraulic conditions affecting the bank, at least relative to conditions that develop when banks are exposed subaerially. Copyright © 2017 John Wiley & Sons, Ltd.